Innovative Design of Practical Tools for Umrah Training by Using QFD and TRIZ. - ADAM, MUHAMMAD IQBAL; Mohammad, PM Ts Dr Musli; Yahya, Mohd Shahir (Research Progress in Mechanical and Manufacturing Engineering, 2022)
: In order to compete at a higher level, products must be innovated by referring to market demands. Some of the engineering tools that can be used in order to improve existing products that meet requirements of the customers are Quality function Deployment (QFD) and Theory of Inventive Problem Solving (TRIZ). This paper is about creating innovative designs of practical tools that have been used during Umrah training by using QFD and TRIZ method. The objectives of this project are: (1) to identify the customer requirements of the portable training set for Umrah course; (2) to evaluate the importance of the product requirements and the performance of existing products and (3) to propose innovative design using QFD and TRIZ. Pilot interview is conducted to identify the customer requirements before the questionnaire can be designed. Data was collected using an online questionnaire survey based on volunteer sampling. The respondents of the survey involved the one who is involved in practical tools design while organizing the practical session of Umrah course. Based on the feedback of the survey, survey analysis is performed by constructing a QFD table and implementing the TRIZ design principle. The new practical tools design is finalised based on the customer and technical requirements. Some of the improvements by the new design were its suitability to be installed whether indoor, outdoor or on any surfaces. Other than that, the design was made in a foldable tent concept which made it compact for storage, portable, light and easy to set up. The improved design had been drawn using Solidworks software. The implementation of the combination of QFD and TRIZ had shown a positive result on the improvement of the practical tools.